Perubahan Sikap pada Anak Sekolah Dasar di Indonesia Tahun 2014-2018 (Gerakan Nusantara) - Dinar Farrasia Hafizhah; Ahmad Syafiq; Sandra Fikawati (Media Kesehatan Masyarakat Indonesia, 2020)
Behavioral patterns and eating habits as adults are formed in childhood. Knowledge and eating habits will lead to changes in a more regular and balanced nutritional attitude. The purpose of this study is to look at the effect of nutrition program education in changes in the average attitude score before and after of Gerakan Nusantara program in 2014-2018. 7605 people are elementary school students grade III, IV, and V in several areas in the City of Jakarta, Bandung, Surabaya, Medan, Makassar, Yogyakarta, Pontianak, NTT, Pekanbaru, Padang, Jambi, and Sorong. The data used are secondary data from Gerakan Nusantara in 2014-2018. Data processing using SPSS with t-test dependent & t-test independent, correlation and One-way Anova. The analysis showed that there was a statistically significant change (p<0.05) in each year with a difference in 2014 related to an increase in attitude by 4%, in 2015 by 6%, in 2016 by 6%, in 2017 by 10%. in 2018 at 36%. Meanwhile, the relationship of knowledge to attitudes obtained statistically significant results (p<0.05), in 2014 (r = 0.47, p = 0,000), 2015 (r = 0.26, p = 0,000), year 2016 (r = 0.35, p = 0,000), 2017 (r = 0.26, p = 0,000) and 2018 (r = 0.41, p = 0,000). Nutrition education programs bring significant improvements in attitude changes that are also influenced by knowledge in primary school children each year.